The Influence of Competence and Knowledge Sharing on Employee Performance with the Mediation of Job Satisfaction at the Department of Trade and Industry of Central Kalimantan Province - Lauran Yuni Silaban; Vivy Kristinae; Ani Mahrita; Meitiana (International Environmental Conferrence on Biosustainability Advancement, 2025)
This study aims to analyze the influence of competence and knowledge sharing on employee performance with job satisfaction as a mediating variable at the Department of Trade and Industry of Central Kalimantan Province. This study uses a quantitative approach with the Partial Least Square (SmartPLS) analysis method. Data were collected through distributing questionnaires to 30 employees as research samples. The results of the analysis show that competence has a significant effect on job satisfaction (p = 0) and employee performance (p = 0) Meanwhile, knowledge sharing has a significant effect on job satisfaction (p = 0.001) but does not have a significant direct effect on employee performance (p = 0.456) Job satisfaction is proven to be able to mediate the effect of competence on employee performance (p = 0) , but does not significantly mediate the effect of knowledge sharing (p = 0.977) These findings emphasize the importance of improving competence and job satisfaction to encourage optimal employee performance.